ADVERSE PREGNANCY OUTCOMES IN SICKLE CELL TRAIT: A PROSPECTIVE COHORT STUDY EVALUATING CLINICAL AND HAEMATOLOGICAL PARAMETERS IN POSTPARTUM MOTHERS AND NEW-BORNS. : Sickle cell trait pregnancy and outcomes - Al-Kindi, r. Salam (Mediterranean Journal of Hematology and Infectious Diseases, 2022)
Abstract – Sickle cell trait (SCT) is a condition caused by the inheritance of a single allele of the abnormal haemoglobin beta gene, HbS. Carriers of SCT are generally asymptomatic, and they do not manifest the haematological and clinical abnormalities of sickle cell anaemia (SCA). However, there is evidence that they display some of the symptoms in stressful situations. Pregnancy is a stressful physiological event, and it is not clear if SCT adversely affects pregnancy outcomes, particularly those from the developing countries, who regularly suffer from nutritional insufficiency. Objective – This study aims to investigate pregnancy outcomes in Sudanese women with SCT. Subjects and methods – Pregnant women with (HbAS, n=34) and without (HbAA, n=60) SCT were recruited during their first trimester by El Obeid Hospital, Kordofan, Western Sudan. Ethical approval from the Faculty of Medicine, University of Khartoum, and informed consent from the participants were obtained. Detailed anthropometric, haematological, clinical, obstetric and birth outcome data were documented. Blood samples were collected at enrolment and delivery. Results – At enrolment, the first trimester, the SCT group did not manifest SCA symptoms, and there was no difference in any of the haematological parameters between the SCT and control groups. At delivery, the women with SCT compared with the control group had lower levels of haemoglobin (Hb, p=0.000), packed cell volume (PCV, p=0.000), mean corpuscular haemoglobin (MCH, p=0.002) and neutrophil counts (p=0.045) and higher mean corpuscular volume (MCV, p=0.000) and platelet counts (p=0.000). Similarly, at delivery, the babies of SCT women had lower birth weight (p=0.000), lower Hb (p=0.045), PCV (p=0.000), MCH (p=0.000) and higher neutrophil (p=0.004) and platelet counts (p=0.000) than the babies of the healthy control group. Additionally, there were more miscarriages, stillbirths and admissions to the Special Care Baby Unit (SCBU) in the SCT group. Conclusions – The study revealed that SCT is associated with adverse pregnancy outcomes, including maternal and neonatal anaemia, low birth weight and increased risk of still birth, miscarriage and admission to SCBU. Therefore, pregnant women with SCT should be regarded as a high-risk group, and given pre-conceptual advice and multidisciplinary antenatal and postnatal care.